HOW THE VETO POWER OF PERMANENT MEMBERS OF UNSC IS AFFECTING THE UN'S PEACEKEEPING OPERATIONS BETWEEN 2010 AND 2025? - Firdavsbek Erkinjonov Eldorjon o'g'li; Richard Caplan; Jovhar Museyibzada (International Journal of Business, Law and Political Science, 2026)
Objective: This study examines the impact of veto power of permanent members of UNSC on the design, mandate strength of the resolutions adopted by the Council. Method: A mixed-method approach was employed, combining a qualitative comparison between the cases of Syria, Ukraine and Gaza and quantitative trend analysis from UNSC resolution, voting records, reports and articles. Results: The results indicate that the veto causes the dilution of mandates, where the threat of P5 prevents the Council from adopting a restrictive and decisive resolution. In the cases of Syria and Gaza, this resulted in significant time delays and the substitution of robust security mandates with limited humanitarian coordination roles. Novelty: The implications of these findings may be that in the absence of institutional reform or voluntary veto restraint, the Security Council may experience complete operational obsolescence when serving to protect civilians in major power contests. While this study focuses on cases that directly or indirectly involve major power interests, its findings are limited to the 2010-2025 timeframe; future research should explore the applicability of this "veto shadow" framework to peacekeeping missions in diverse geographic contexts, where permanent member involvements were less polarised.